Anaphylactoid Reaction Against to Atropine - Melike Korkmaz Toker; Ayşe Gül Karabay; Aykan Gülleroğlu; Gökalp Gündoğdu; İlhan Güney Biçer; Mustafa Tayfun Aldemir (Galenos Yayinevi, 2014)
In this case report, the anaphylactoid reaction against to atropine had been reported in a 51 years old woman patient who had undertaken to total abdominal hystrectomy and bilateral salphingooferectomy surgery. At the end of the surgery, the anesthesia maintenance finished during the extubation procedure consequtively atropine had given intravenously 0,01 mg.kg-1 for preventing the neostigmine's cholinergic effects. After the enjection of atropine tachycardia occured, nonpitting edema, maculopapular skin rash beginning from the periferal veins especially head and neck region spread out althrough the body observed. Anaphylactoid reaction developing like angioedema at the head and neck region threated the airway safety, therefore methylprednisolone 4 mg.kg-1, ranitidine 50 mg and feniramine maleat 1 mg.kg-1 intravenously administered. For safety of the airway the patient transferred to intensive care unit as intubated. After 24 hours follow up patient had clinically recovered and extubated. With our case report we try to emphasise the anaphylactoid reaction against to atropine and raise awareness of the anesthesiologists.